2016
DOI: 10.1073/pnas.1525139113
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating structural proteins in viral “dark matter” with metaproteomics

Abstract: Viruses are ecologically important, yet environmental virology is limited by dominance of unannotated genomic sequences representing taxonomic and functional "viral dark matter." Although recent analytical advances are rapidly improving taxonomic annotations, identifying functional dark matter remains problematic. Here, we apply paired metaproteomics and dsDNA-targeted metagenomics to identify 1,875 virion-associated proteins from the ocean. Over onehalf of these proteins were newly functionally annotated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 61 publications
6
85
0
Order By: Relevance
“…31). The capsid protein encoded by gene 9 of vSAGs 37-F6 was homologous to these unknown abundant capsid proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…31). The capsid protein encoded by gene 9 of vSAGs 37-F6 was homologous to these unknown abundant capsid proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A functional annotation of all GOV predicted proteins was based on a comparison to the PFAM domain database (v27 64 ) with HmmSearch 65 (threshold of 30 on bit score and 1e-3 on e-value), and additional putative structural proteins were identified through a BLAST comparison to protein clusters detected in viral metaproteomics dataset 66 . This metaproteomics dataset led to the annotation of 13,547 hypothetical proteins lacking a PFAM annotation.…”
Section: Viral Contigs Annotationmentioning
confidence: 99%
“…We observed that viral structural proteins comprised the majority of the viral proteins (86%) in the VCs (Supporting Information Table S2), which was consistent with findings from a previous viral metaproteomic study (Brum et al ., ). We used the same method as them to map the Pacific Ocean virome (POV) dataset to obtain the eight most abundant PCs which accounted for half of the spectra counts (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
“…B). As the taxonomic distribution observed in a previous study (Brum et al ., ), myoviruses, podoviruses and siphoviruses were the major viral families, accounting for 21%, 15% and 3% of the viral spectra (Fig. B).…”
Section: Resultsmentioning
confidence: 99%